2015
DOI: 10.1249/mss.0000000000000660
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Tissue Insulin Action and IL-6 Signaling after Exercise in Obese Mice

Abstract: The results suggest a link between exercise-induced increases in IL-6, reductions in indices of M1 macrophages, and increased IL-10, a reputed anti-inflammatory cytokine with insulin-sensitizing properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 39 publications
(60 reference statements)
6
45
0
Order By: Relevance
“…Oliveira et al (2013) found that acute swim exercise led to reductions in markers of M1, pro-inflammatory macrophages, and increases in anti-inflammatory M2 macrophages in adipose tissue from rats fed a high-fat diet. Consistent with these findings, MacPherson et al (2015) reported reductions in indices of M1 macrophages, via quantitative polymerase chain reaction and immunofluorescence, in inguinal subcutaneous adipose tissue from mice fed a high-fat diet following a single bout of treadmill running.…”
Section: Does Acute Exercise Reduce Inflammation and Improve Glucose supporting
confidence: 61%
See 2 more Smart Citations
“…Oliveira et al (2013) found that acute swim exercise led to reductions in markers of M1, pro-inflammatory macrophages, and increases in anti-inflammatory M2 macrophages in adipose tissue from rats fed a high-fat diet. Consistent with these findings, MacPherson et al (2015) reported reductions in indices of M1 macrophages, via quantitative polymerase chain reaction and immunofluorescence, in inguinal subcutaneous adipose tissue from mice fed a high-fat diet following a single bout of treadmill running.…”
Section: Does Acute Exercise Reduce Inflammation and Improve Glucose supporting
confidence: 61%
“…In support of this, IL-6 mRNA expression and markers of IL-6 signaling such as SOCS3 (suppressor of cytokine signaling 3) mRNA and signal transducer and activator of transcription 3 phosphorylation are increased in parallel with reductions in M1 macrophages and increases in insulin-stimulated Akt phosphorylation in inguinal adipose tissue from obese mice (MacPherson et al 2015). In contrast to higher intensity exercise in lean, healthy animals, the induction of IL-6 signaling with exercise in adipose tissue from obese mice occurs independent of increases in classically identified markers of inflammation such as TNFα and c-Jun N-terminal kinase phosphorylation.…”
Section: Is There a Common Mechanism That Explains The Protective Effmentioning
confidence: 92%
See 1 more Smart Citation
“…Exercise is an emerging pro-myelination therapeutic intervention for many pathologies including demyelinating disease (Sampaio-Baptista et al, 2013;Scholz et al, 2009) and is associated with elevated BDNF levels and increased neuronal activity (Gold et al, 2003). Exercise can shift macrophage polarization from an M1 to an M2 state (Goh and Ladiges, 2014;Macpherson et al, 2015) and be used as a preemptive strategy to mitigate demyelinating disease (Bernardes et al, 2016). Whether it has an identical molecular signature and impact as direct nerve stimulation remains to be determined, but is promising as a non-interventional adjunct therapy.…”
Section: Potential Mechanisms Regulating Macrophage Switch From M1 Tomentioning
confidence: 99%
“…Approximately 100 mg of eWAT and scAT were fixed in 10% neutral-buffered formalin (VWR, Mississauga, ON, Canada), dehydrated in 70% ethanol (Fisher Scientific), and embedded in paraffin. Five micrometer sections were mounted on 1.2 mm Superfrost slides, stained with Harris hematoxylin and eosin stock (H&E; Fisher Scientific) and imaged (Olympus FSX 100 light microscope, Olympus, Tokyo, Japan) as previously described (MacPherson et al 2015). Cells were sampled in each image to determine cross-sectional area (>200 cells/mouse) (ImageJ software, National Institute of Mental Health, Bethesda, MD).…”
Section: Histologymentioning
confidence: 99%